2005
DOI: 10.1038/ja.2005.67
|View full text |Cite
|
Sign up to set email alerts
|

FR258900, a Novel Glycogen Phosphorylase Inhibitor Isolated from Fungus No. 138354

Abstract: A novel glycogen phosphorylase inhibitor FR258900 was isolated from the cultured broth of a fungal strain No. 138354. We examined the hypoglycemic effects of FR258900 in diabetic animal models. FR258900 treatment significantly reduced the plasma glucose concentrations during oral glucose tolerance tests in diabetic mice models, including db/db mice and STZinduced diabetic mice. Furthermore, FR258900 treatment resulted in rapid decrease in the plasma glucose levels in db/db mice. These improvements in glucose d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…FR258900 is a 23-carbon pentanedioic acid that binds to the AMP site of glycogen phosphorylase and stabilizes its inactive conformation 87 . This compound significantly decreased plasma glucose levels and increased hepatic glycogen levels in db/db and streptozocin-induced diabetic mouse models 31 , but long-term effects or actions in other tissues were not studied. CP-316,819, is an indole carboxamide compound 32 that decreased hepatic glucose output in fasted dogs with basal or elevated glucagon levels 33 , although thorough analysis of potential effects on other tissues was not performed.…”
Section: Strategies To Modulate Liver Glucose and Glycogen Metabolismmentioning
confidence: 99%
“…FR258900 is a 23-carbon pentanedioic acid that binds to the AMP site of glycogen phosphorylase and stabilizes its inactive conformation 87 . This compound significantly decreased plasma glucose levels and increased hepatic glycogen levels in db/db and streptozocin-induced diabetic mouse models 31 , but long-term effects or actions in other tissues were not studied. CP-316,819, is an indole carboxamide compound 32 that decreased hepatic glucose output in fasted dogs with basal or elevated glucagon levels 33 , although thorough analysis of potential effects on other tissues was not performed.…”
Section: Strategies To Modulate Liver Glucose and Glycogen Metabolismmentioning
confidence: 99%
“…This position prevents the crucial conformational changes that take place on activation of the enzyme that are critical for catalytic activity and create the phosphate recognition site. Residues that contribute to the catalytic site come from 6 (134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149)(150), 13 (371-376), and 18 (478-484) in domain 1 and from 19 (562-570), the loop (571-574) between 19 (562-570) and 18 (575-593), and the loop (666-675) between 22 (661-665) and 21 (676-684) in domain 2 [48][49][50]. On transition from T state to R state (activation of the enzyme), the 280s loop becomes disordered and displaced, opening a channel that allows a crucial residue, Arg569, to enter the catalytic site in place of Asp283 and create the recognition site for the substrate phosphate; that also allows access of the glycogen substrate to reach the catalytic site and promotes a favourable electrostatic environment for the 5'-phosphate of the essential cofactor pyridoxal-5'-phosphate (PLP); the substrate phosphate site is within hydrogen-bonding distance of the 5'-phosphate group of PLP [51][52][53][54] volves movement of the 380s loop (377-384) which results in closure of the catalytic site and creation of the recognition site for oligosaccharide [55].…”
Section: Catalytic Sitementioning
confidence: 99%
“…13835, FR258900 was shown to inhibit HLGPa [136]. The compound proved effective in lowering plasma glucose levels in animal models of diabetes [137]. The structure of the co-crystallised GPb-FR258900 complex [138], determined to 2.2 Å resolution, revealed that FR258900 binds at the allosteric site where the natural allosteric activator AMP, and the natural allosteric inhibitor Glc-6-P bind.…”
Section: Allosteric (Or Amp-binding) Sitementioning
confidence: 99%
“…The compound exhibited a potent inhibitory action on human liver GPa (hlGPa), and significantly reduced the plasma glucose concentrations in diabetic mice models. These effects were accompanied by increased liver glycogen contents (Furukawa et al 2005b), suggesting that it may activate glycogen synthesis via glycogen phosphorylase inhibition and therefore provide a new potential anti‐hyperglycemic agent.…”
mentioning
confidence: 99%